Climate Change Impacts on Household Food Security in Sri Lanka’s Dry Zones: A Qualitative Analysis - Sisira Kumara Naradda Gamage; Solanga Arachchige U. Niranjala; Jayasooriya Mudiyanselage Harshana M. Upulwehera; Allayarov Piratdin; Kumara Bandage Thilini Udesha K. Bandara; Hatharakorale Gedara Kolitha N. Bandara; Hetti Arachchige Buddhika W. Hettiarachchi; Adikari Mudiyanselage P. Adikari; Sumanapalage D. Amasha Sumanapala; Manamendra K. Nilakshi Pabasara; Ran Pathige Indika R. Prasanna (Challenges, 2025)
Climate change is a substantial threat to worldwide food security, affecting the supply, stability, accessibility, and quality of food. This study aimed to explore the impact of climate change on household food security of farming communities in dry zones in Sri Lanka, focusing on water resource limitations and agricultural productivity, using a qualitative case study method with 13 cases. The impact of climate change on farming and food security was identified under the key themes of food production and yield, income and economic stability, water resources and management, food availability and access, nutrition quality, and dietary diversity. The findings revealed that climate change can indirectly affect food security by impacting household and personal incomes. It also influences health, access to clean water, and the ability to utilize food effectively. Such climatic changes significantly impact household food security and distinctly affect nutrition quality and dietary diversity, which are identifiable as the primary food security elements. This study suggests moving other income sources to enhance the economic stability of farming households, adopting new farming techniques, organizing government assistance programs, and establishing social safety nets such as food aid programs and financial support for affected households. Such activities will help to address the decline of yield production that is caused by climate change, and will mitigate the effect that climate change has on household food security. It further emphasizes the need to combine modern policy interventions and the existing domestic adaptation framework. This investigation employs a qualitative research method to explore how communities experience actual climate change effects, including water issues and farm failures. It effectively captures and contributes detailed knowledge to the current research on this subject.